‘Cosmovillagers’ as Sustainable Rural Development Actors in Mountain Hamlets? International Immigrant Entrepreneurs’ Perceptions of Sustainability in the Lleida Pyrenees (Catalonia, Spain) - Morén-Alegret, Ricard (2022)
In recent decades, small villages in some mountainous regions in Europe have been suffering from ageing and depopulation, yet at the same time, immigrants have been arriving and settling there. This paper sheds light on the perceptions of sustainable rural development among international immigrants living in municipalities with fewer than 500 inhabitants, which are already the home to some ‘cosmovillagers’. If immigrants’ views are left unattended, an important part of reality will be lacking in the picture of mountainous areas because today immigration is qualitatively relevant in rural Europe. This paper aims to answer the following questions, among others: What dimensions of sustainability are underscored? What are the main challenges for sustainability and the proposals for improvement? What are the local sustainability challenges? This paper provides research results and insights based on original data gathered during fieldwork in the Pyrenees as well as analyses of documents, maps and statistics. Specifically, the main focus is on some several sparsely populated areas in the Lleida Pyrenees, e.g. dozens of municipalities in Alt Urgell, Cerdanya, Pallars Sobirà and Val d’Aran. Thus this paper aims to help fill that relative gap in the existing academic literature by offering original qualitative information.